Phenomenal Experiences, First-Person Methods, and the Artificiality of Experimental Data. Issue 5 (December 2014) - Feest, Uljana
Abstract : While philosophical discussions of first-person methods often turn on the veridicality of first-person reports, I argue that more attention should be paid to the circumstances and aims of their experimental production in the science of perception. After pointing to the 'constructedness' of first-person reports, I raise questions about the criteria by which to judge whether they illuminate something about the nature of perception. I illustrate this point with a historical debate between Gestalt psychologists and atomists, both of whom used first-person methods to investigate perception, but who disagreed deeply over the epistemic value of their respective first-person data.